Endometriosis and Infertility: Mechanisms and therapeutic approaches - a literature review (Research, Society and Development, 2024)
Introduction: Endometriosis is a chronic gynecological condition affecting about 10% of women of reproductive age and is a leading cause of female infertility. The relationship between endometriosis and infertility is complex, involving anatomical, inflammatory, immunological, and hormonal factors. Objective: This article aims to review the existing literature on the mechanisms by which endometriosis causes infertility and the therapeutic approaches available to treat this condition. Methodology: A systematic literature review was conducted using databases such as PubMed, Scopus, and Web of Science. Studies addressing the mechanisms of infertility associated with endometriosis and therapeutic interventions, including medical, surgical treatments, and assisted reproductive techniques, were included. Results: The review identified that endometriosis causes infertility through mechanisms such as fallopian tube obstruction, pelvic adhesions, altered oocyte quality, and endometrial dysfunction. Medical treatments, such as hormonal contraceptives and GnRH agonists, are effective in managing symptoms but have limitations in restoring fertility. Surgical interventions, such as laparoscopy, are effective in removing endometriotic lesions and restoring pelvic anatomy. Assisted reproductive techniques, such as in vitro fertilization (IVF), have shown efficacy in improving pregnancy rates in women with endometriosis. Conclusion: Endometriosis is a significant cause of female infertility with multiple underlying mechanisms. Therapeutic approaches vary according to the severity of the disease and the patient's reproductive goals. A combination of medical, surgical treatments, and assisted reproductive techniques offers the best chance of success for women with endometriosis who wish to conceive. Future studies should focus on emerging therapies and optimizing existing approaches.